Comprehensive overview of the toxicities of small-molecule cryoprotectants for carnivorous spermatozoa: foundation for computational cryobiotechnology - Karimi, Isaac; Mohammad, Layth Jasim; Suvitha, A.; Haidari, Zohreh; Schiöth, Helgi B. (Frontiers in Toxicology, 2025)
BackgroundThe specific and non-specific toxicities of cryoprotective agents (CPAs) for semen or spermatozoa cryopreservation/vitrification (SC/SV) remain challenges to the success of assisted reproductive technologies.ObjectiveWe searched for and integrated the physicochemical and toxicological characteristics of small-molecule CPAs as well as curated the information of all extenders reported for carnivores to provide a foundation for new research avenues and computational cryobiology.MethodsThe PubMed database was systematically searched for CPAs reported in SC/SV of carnivores from 1964 to 2024. The physicochemical features, ADMET parameters, toxicity classes, optimized structures, biological activities, thermodynamic equilibrium constants, and kinetic parameters were curated and assessed computationally.ResultsSixty-two relevant papers pertaining to CPAs used in SC/SV were found, and 11 CPAs were selected. Among the properties of CPAs, the molecular weight range (59–758 g/mol), melting point (−60°C to 236°C), XlogP3 (−4.5 to 12.9), topological polar surface area (TPSA; 20–160 Å2), Caco2 permeability (−0.62 to 1.55 log(Papp) in 10–6 cm/s), volume of distribution (−1.04 to 0.19 log L/kg), unbound fraction of a CPA in plasma (0.198–0.895), and Tetrahymena pyriformis toxicity (log µg/L; −2.230 to 0.285) are reported here. Glutathione, dimethyl formamide, methyl formamide, and dimethyl sulfoxide were used as the P-glycoprotein substrates. Ethylene glycol, dimethyl sulfoxide, dimethyl formamide, methyl formamide, glycerol, and soybean lecithin showed Caco2 permeabilities in this order, whereas fructose, glutathione, glutamine, glucose, and citric acid were not Caco2-permeable. The CPAs were distributed in various compartments and could alter the physiological properties of both seminal plasma and spermatozoa. Low volume distributions of all CPAs except glucose indicate high water solubility or high protein binding because higher amounts of the CPAs remain in the seminal plasma.ConclusionADMET information of the CPAs and extenders in the bipartite compartments of seminal plasma and intracellular spaces of spermatozoa are very important for systematic definition and integration because the nature of the extenders and seminal plasma could alter the physiology of cryopreserved spermatozoa.